2013
DOI: 10.1021/jp406603q
|View full text |Cite
|
Sign up to set email alerts
|

Fractal TiO2 Nanostructures by Nonthermal Laser Ablation at Ambient Pressure

Abstract: Fractal TiO 2 nanostructures in crystalline form are obtained at ambient pressure and temperature by pulsed laser deposition with femtosecond pulses. The synthesized structures have been studied by scanning electron microscopy, Raman spectroscopy, and X-ray photoemission spectroscopy. We show that the dendritic aggregations deposited on silicon wafers at room temperature are fractals. They are composed by nanoparticles with an average diameter in a range below 20 nm, with the presence of larger nanoparticles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Moreover, the techniques outlined in this work will find applications in a variety of fields of interest for nanotechnology. Few-cycle AFM will be useful to characterize the mechanical contact properties of nanostructures produced by femtosecond laser ablation [ 22 ], while wavelets techniques will be of relevance in inspecting the time dynamics of oscillatory modes and their phase relations in picosecond acoustic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the techniques outlined in this work will find applications in a variety of fields of interest for nanotechnology. Few-cycle AFM will be useful to characterize the mechanical contact properties of nanostructures produced by femtosecond laser ablation [ 22 ], while wavelets techniques will be of relevance in inspecting the time dynamics of oscillatory modes and their phase relations in picosecond acoustic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al [24] showed that by using a jet of Ar gas directed across the ablation target it was possible to deposit silver NP films at up to 20 mm from the target in Ar at atmospheric pressure, and these films were effective for SERS. Cavaliere et al [25] have recently carried out fs-PLD of TiO 2 at ambient pressure and room temperature. In this study the substrate was placed at a 30 • angle with respect to the target surface to allow access of the laser beam, and the target-substrate separation was 2-4 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide semiconductors are doped with either noble metals like silver [6] and gold [7], coupled with narrow band gap semiconductors, or carbon-based material like graphene [8] to shift their absorption to the Vis spectral region or improve their conductivity. Based on these facts, a green, fast, and optical technique [24] known as pulsed laser ablation in liquid (PLAL) has been proved very beneficial in synthesizing metal semiconductor nanocrystals such as chalcogenides like CdSe [25] and oxide semiconductors like TiO 2 [26,27], CuO [28,29], and ZnO [30,31]. Its limitation includes selfoxidation of its photogenerated holes, aggregation to form larger particles reducing its surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods like successive ionic layer adsorption and reaction (SILAR) [20], surface-functionalized method [21], chemical vapor deposition [22], and metalosilicate support [23] have been tried to produce heterojunctions of TiO 2 /CdS either in the form of thin films or nanoparticles, but most of these methods require the use of high vacuum, multistep/tedious process, production of chemical by-products, and the use of special solvents. Based on these facts, a green, fast, and optical technique [24] known as pulsed laser ablation in liquid (PLAL) has been proved very beneficial in synthesizing metal semiconductor nanocrystals such as chalcogenides like CdSe [25] and oxide semiconductors like TiO 2 [26,27], CuO [28,29], and ZnO [30,31]. This method, capable of making and breaking bonds, has been applied in synthesizing and oxidizing nanocomposite structure of TiO 2 /CdS.…”
Section: Introductionmentioning
confidence: 99%